UNSUR BUDAYA MATERIAL DALAM NOVEL ENTROK KARYA OKKY MADASARI - Hikmasari, Miftahurohmah; Sahayu, Wening (Balai Bahasa Jawa Timur, 2019)
This research aims to classify the term of material culture containing in the Entrok novel written by Okky Madasari. This research also provided an analysis related to the underlying reason for the cultural terms which are included in the category of the terms of material culture. In particular, the discussed problems in the present research involve the terms of material culture which only exist in Indonesia and mostly related to the Javanese culture. This research is qualitative descriptive research. The result shows that there are six categories of material culture terms consisting of food, house, clothes, transportation, daily equipment, and art instruments. The findings reveal 53 terms dividing into: (1) 25 food terms, (2) 10 houses terms, (3) 9 clothes terms, (4) 3 transportation terms, (5) 3 daily equipment terms, and (6) 3 art instruments terms. These terms are material culture terms representing the characteristic of Indonesian culture.